2007
DOI: 10.1007/s00259-006-0324-y
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and in vivo evaluation of a novel 5-HT1A receptor agonist radioligand [O-methyl-11C]2-(4-(4-(2-methoxyphenyl)piperazin-1-yl)butyl)-4-methyl-1,2,4-triazine-3,5(2H,4H)dione in nonhuman primates

Abstract: We identified [11C]MMP as an optimal agonist PET tracer that shows quantifiable, specific binding in vivo to 5-HT1A receptors in baboons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
51
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 48 publications
2
51
1
Order By: Relevance
“…Compared to 8-OH-DPAT, CUMI-101 has higher affinity ( K i = 0.15 nM), better selectivity for 5-HT 1A R, and it is a partial agonist (E max = 88%; EC 50 = 0.1 nM, Kumar et al, 2007). It therefore has the potential to be both a PET tracer and when tritiated, a ligand for in vitro studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to 8-OH-DPAT, CUMI-101 has higher affinity ( K i = 0.15 nM), better selectivity for 5-HT 1A R, and it is a partial agonist (E max = 88%; EC 50 = 0.1 nM, Kumar et al, 2007). It therefore has the potential to be both a PET tracer and when tritiated, a ligand for in vitro studies.…”
Section: Introductionmentioning
confidence: 99%
“…We have developed [O-Methyl- 11 C]2-(4-(2-methoxyphenyl)piperazin-1-yl)butyl)-4- methyl-1,2,4-triazine-3,5(2H,4H)dione ([ 11 C]CUMI-101; Figure 1) and reported its properties as a specific 5-HT 1A R partial agonist PET tracer in human and nonhuman primates (Kumar et al, 2012; Kumar et al, 2011; Kumar et al, 2007; Milak et al, 2008; Milak et al, 2010; Milak et al, 2011). Compared to 8-OH-DPAT, CUMI-101 has higher affinity ( K i = 0.15 nM), better selectivity for 5-HT 1A R, and it is a partial agonist (E max = 88%; EC 50 = 0.1 nM, Kumar et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…A 2007 study reported the initial synthesis and in vivo evaluation of a potential agonist 5-HT 1A receptor radioligand, 11 C-CUMI-101 (4). In baboons, 11 C-CUMI-101 was shown to have optimal brain uptake, good washout, and a plasma free fraction of 60% (5).…”
mentioning
confidence: 99%
“…In baboons, 11 C-CUMI-101 was shown to have optimal brain uptake, good washout, and a plasma free fraction of 60% (5). CUMI-101 exhibited agonist-like properties by dose-dependently stimulating 35 S-GTPγS (GTP is guanosine triphosphate) binding in recombinant Chinese Hamster Ovary (CHO) cells expressing human 5-HT 1A receptor (4). In contrast, a recent study showed that, in native rat brain tissues, CUMI-101 behaved as a potent 5-HT 1A receptor antagonist (6).…”
mentioning
confidence: 99%
“…The preparation of 3-[4-(2-methoxyphenyl)piperaziny-1-yl]propan-1-ol (2) was performed by alkylation of 1-(2-methoxyphenyl)piperazine using 3-bromo-1-propanol as alkylating agent. The reaction was carried out in anhydrous CH 3 Figure 1. The paper electrophoresis pattern of 99m TcN-MPPC remained at the point of spotting, suggesting that it is a neutral complex.…”
Section: Chemistrymentioning
confidence: 99%